KAJIAN LITERATUR: PEMANFAATAN BAHAN KAYA ANTIOKSIDAN, SERAT, DAN PATI RESISTEN PADA PRODUK MI - Michelle, Michelle; Anugrahati, Nuri Arum (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2022)
ABSTRACTChronic diseases such as stroke, cancer, and diabetes can cause death to up to 71% of the world every year. A healthy lifestyle is essential in reducing the risk of chronic disease, including eating foods that contain functional components such as antioxidants, fiber, and resistant starch. Noodles are a popular food in more than 80 countries, making them an ideal functional food to be developed with the addition of food ingredients. This review aimed to examine the effect of ingredients rich in antioxidants, fiber, and resistant starch on noodle products and determine the optimal concentration that panelists can accept from adding these ingredients to noodles. Ingredients that can increase the antioxidant content of noodles are linseed, pomelo, banana, black carrot, oyster mushroom, Moringa leaves, beets, and marigolds. Fiber-rich ingredients that can be used in making noodles are chickpeas, oyster mushrooms, red spinach, moringa leaves, beets, Rc-298 bran, green okra, and purple sweet potatoes. Ingredients that can increase the content of resistant starch are pomelo, linseed, pineapple stems, and kidney beans. The concentration of foods rich in antioxidants, fiber, and resistant starch is directly proportional to the content of antioxidants, fiber, and resistant starch in noodles. However, this can lead to an increase in cooking loss, cooking time, and water absorption, as well as a decrease in preferences for the parameters of taste, aroma, appearance, texture, and overall acceptance. The optimal concentrations of food ingredients that were acceptable to panelists for noodle products were 4% oyster mushrooms, 5% pomelo dried segments, 10% black carrots, and 5% linseed.Keywords: Antioxidant, noodles, functional food, resistant starch, fiber.ABSTRAKPenyakit kronis seperti stroke, kanker, dan diabetes dapat menyebabkan kematian hingga 71% di dunia setiap tahunnya. Gaya hidup sehat sangat penting dalam mengurangi risiko penyakit kronis. Salah satu cara untuk mengurangi risiko penyakit kronis adalah dengan mengonsumsi bahan pangan yang mengandung komponen fungsional seperti antioksidan, serat, dan pati resisten. Mi merupakan makanan populer di lebih dari 80 negara sehingga mi menjadi makanan fungsional yang ideal untuk dikembangkan dengan penambahan bahan pangan. Kajian literatur ini bertujuan untuk mengaji pengaruh bahan kaya antioksidan, serat, dan pati resisten pada produk mi dan menentukan konsentrasi optimal yang dapat diterima panelis dari penambahan bahan tersebut pada mi. Bahan yang dapat meningkatkan kandungan antioksidan pada mi adalah linseed, pomelo, pisang, wortel hitam, jamur tiram, daun kelor, bit, dan marigold. Bahan kaya serat yang dapat digunakan dalam pembuatan mi adalah chickpea, jamur tiram, bayam merah, daun kelor, bit, bekatul varian Rc-298, okra hijau, dan ubi jalar ungu. Bahan yang dapat meningkatkan kandungan pati resisten adalah pomelo, linseed, batang nanas, dan kacang merah. Konsentrasi bahan pangan yang kaya antioksidan, serat, dan pati resisten yang lebih tinggi meningkatkan kandungan antioksidan, serat, dan pati resisten pada mi. Namun, hal tersebut dapat menyebabkan peningkatan cooking loss, cooking time, dan water absorption, serta penurunan preferensi dari parameter rasa, aroma, penampilan, tekstur, dan overall acceptance. Konsentrasi optimal bahan pangan yang dapat diterima panelis pada produk mi adalah 4% jamur tiram, 5% pomelo dried segments, 10% wortel hitam, dan 5% linseed.Kata kunci: antioksidan, mi, pangan fungsional, pati resisten, serat.